Identification of spinach SIAMESE and analysis of its function in plant immunity. Issue 2 (3rd April 2017) - Wang, Tianhua; Song, Teng; Xu, Chenxi; Cai, Xiaofeng; Wang, Xiaoli; Ma, Huimin; Zhou, Jianjian; Ge, Chenhui; Wang, Quanhua; Wang, Shui
Abstract: Diseases cause a significant loss in both yield and quality of spinach. The cell cycle signalling pathway plays a central role in balancing development and immunity of plants. Cyclin-Dependent Kinase Inhibitor (CKI) is a core cell cycle regulator. It has been found that two Arabidopsis CKIs, SIAMESE (SIM) and SMR1 (SIAMESE-Related 1), function redundantly not only as negative regulators of cell proliferation but also as positive regulators of plant immunity. In the spinach genome, we identified a homologue of Arabidopsis SIM, referred to as Spinacia oleracea SIAMESE (SoSIM). To investigate the function of SoSIM, we introduced the 35S promoter-driven SoSIM ( 35S:SoSIM ) into Arabidopsis sim smr1 double mutants. Over-expression of SoSIM phenocopied RNA interference of Cyclin-Dependent Kinase A1 ( CDKA1 ) which exhibited dwarf and serrated leaves, confirming that SIM is a CDK inhibitor. Arabidopsis wild-type trichomes are single and unicellular, whereas sim smr1 mutant trichomes are clustered and multicellular. SoSIM restored wild-type trichome phenotype of sim smr1 mutant. The sim smr1 mutants were susceptible to the avirulent pathogen Pseudomonas syringae pv. maculicola as compared with wild-type plants. Our data showed that the resistance of 35S:SoSIM -transgenic sim smr1 lines to the pathogen was fully restored, indicating that SoSIM activates plant immunity. These data verify that SoSIM functions as its Arabidopsis counterpart in inhibition of plant development and activation of plant immunity. Therefore, SoSIM can be explored to control the balance between development and immunity in spinach.